Application of Sulfur-2,4-dinitrophenylhydrazine as Modifier for Producing an Advantageous Concrete - Khayit Turaev; Dilnoza Shavkatova; Nodira Amanova; Mohanad Hatem Shadhar; Elyor Berdimurodov; Nessipkhan Bektenov; Ahmad Hosseini-Bandegharae (مجلة بغداد للعلوم)
In this investigative endeavor, a novel concrete variety incorporating sulfur-2,4-dinitrophenylhydrazine modification was developed, and its diverse attributes were explored. This innovative concrete was produced using sulfur-2,4-dinitrophenylhydrazine modification and an array of components. The newly created sulfur-2,4-dinitrophenylhydrazine modifier was synthesized. The surface texture resulting from this modifier was examined using SEM and EDS techniques. The component ratios within concrete, chemical and physical traits derived from the sulfur-2,4-dinitrophenylhydrazine modifier, chemical and corrosion resistance of concrete, concrete stability against water absorption, concrete resilience against freezing, physical and mechanical properties, durability, elastic modulus, and thermal expansion coefficient of the examined sulfur-infused concrete were assessed. The acquired results also substantiated that the thermal expansion coefficient value for sulfur-2,4-dinitrophenylhydrazine modified concrete was 14.8×10-6/0C. The average deformation of the analyzed concrete was 0.0026-0.0051, indicating a superior deformation performance compared to conventional concretes. Concrete with smaller aggregate sizes exhibited greater density, specifically 2283 kg/m3. The concrete density decreased gradually with an increase in aggregate size. The stability of sulfur-2,4-dinitrophenylhydrazine modified concrete was remarkably high in various aggressive environments. EDS analysis revealed that carbon atoms constituted 56.63% of the total mass, while sulfur made up 33.91% of the total mass. The obtained SEM outcomes demonstrated that the sulfur-2,4-dinitrophenylhydrazine modifier exhibited a more porous structure, devoid of crystalline formations. The sulfur-2,4-dinitrophenylhydrazine modification experienced a single-stage thermal mass loss, with the mass loss events being endothermic in nature. The IR findings verified the presence of amino functional groups (connected melamine ring) and the establishment of polymer sulfur chains.